Percy Jackson and the Titan's curse - Riordan, Rick (Puffin books: London, 2007)
The third book in the bestselling Percy Jackson and the Olympians series. Now with a new cover look! Discover the story behind the Disney+ series. The third book in the bestselling Percy Jackson and the Olympians series. Now with a new cover look! Discover the story behind the Disney+ series. HALF BOY - HALF GOD - ALL HERO. It's not every day you find yourself in combat with a half-lion, half human. . . Percy Jackson has a lot on his plate. A powerful goddess has gone missing. The Greek gods are on the brink of war with the Titans. And there's the minor threat of a mystery beast that could destroy Mount Olympus forever. This time, Percy's going to need help and he's found two powerful demigods for the job. . .There's just the small problem of the prophecy. The one that has predicted not all of them will survive. But when you're the son of a Greek god, it happens. Right? Return to the World of Percy Jackson in the best-selling, brand-new adventure featuring the original hero in Percy Jackson and the Olympians- Chalice of the Gods - out now! And don't miss the trio's next adventure in Percy Jackson and the Olympians- Wrath of the Triple Goddess, coming soon!
Keywords: English, Fiction